Introduction to forest ecosystem science and management (John Wiley & Sons, 2003)
Conveying the wide-ranging scope of forestry and the great challenges that lie ahead, this Third Edition brings together leading forestry experts and gives readers a broad overview of the field. Coverage ranges from the basic cell, individual trees, and the forest stand, to management of the forest stand and acquisition of goods and services from the forest.